2017
DOI: 10.5755/j01.ms.23.2.15103
|View full text |Cite
|
Sign up to set email alerts
|

Reducing CO2 Emissions in the Production of Porous Fired Clay Bricksks

Abstract: A plan to reduce CO2 emissions is a priority these days. Brick industry contributes to the increase of these emissions mainly through the use of combustible pore-forming agents such as sawdust, cellulose, and coal sludge. These agents are used to improve the thermal insulation properties of brick products, and the suppliers regularly increase the prices of these agents based on their high consumption. Therefore, in an effort to reduce raw material expenses and CO2 emissions, brick manufacturers are looking for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Many researchers have investigated clay bricks with various additives incorporated into them . The motivations for researchers adding materials to clay bricks include resource conservation, energy and emissions reduction, waste management, and modifications of the physical and thermal properties of the fired brick, among others . Sani and Nzihou concluded that adding organic wastes to clay bricks reduced the energy required to fire the bricks, and they lowered their thermal conductivity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many researchers have investigated clay bricks with various additives incorporated into them . The motivations for researchers adding materials to clay bricks include resource conservation, energy and emissions reduction, waste management, and modifications of the physical and thermal properties of the fired brick, among others . Sani and Nzihou concluded that adding organic wastes to clay bricks reduced the energy required to fire the bricks, and they lowered their thermal conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…Most researchers used one of three types of additives: organic additives, ash, and inorganic (non‐ash) additives. Examples of organic additives that have been used in clay bricks include several types of biomass and sludge, including wheat straw , sunflower seed cake , olive stone flour , sawdust , tobacco , grass , water hyacinth , sewage sludge , mushroom compost , paper pulp , pomace from the winery industry , and olive mill waste , among others . Examples of ashes used as additives in clay bricks include sugarcane bagasse ash , biochar , ash from incinerators and from coal‐fired power plants , rice husk ash , and wood ash .…”
Section: Introductionmentioning
confidence: 99%
“…The chemical composition of brick samples in Table 3 corresponds to the usual contents of the main elements in brick clay [ 57 ]. According to the chemical composition of the stone samples, the stones could probably belong to granite type [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…In spite of the clay minerals are used by thousand years their study and examination are in the focus of research in several segments of science [3][4][5][6][7][8][9][10] and industry [11][12][13][14][15][16][17][18] until today. In our days the brick and ceramic roof tiles industries are the largest user of the conventional brick clays [19][20][21][22][23][24][25][26][27][28][29]. In spite of the large production volume of brick and ceramic roof tile industries and intensive research of the conventional brick clays the drying sensitivity and material structure inhomogeneity can be reason of the scrap formations and quality defaults.…”
Section: Introductionmentioning
confidence: 99%